1987
DOI: 10.1172/jci113138
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of increased alpha adrenergic vasoconstriction in human essential hypertension.

Abstract: Multiple components of vascular alpha adrenergic responsiveness were investigated in twenty-four men with mild hypertension and eighteen age-and weight-matched normotensive controls. Arterial plasma norepinephrine (paNE), an index of sympathetic drive, was increased in hypertensives compared to normotensives (mean±SE), 199±24 vs. 134±11 pg/ml, P < 0.02. The effective concentration of intra-arterial (iaNE) We interpret these data as evidence for normal vascular alpha-receptor sensitivity to norepinephrine in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
68
1
1

Year Published

2001
2001
2007
2007

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 174 publications
(75 citation statements)
references
References 27 publications
5
68
1
1
Order By: Relevance
“…These observations in favour of an a 1 -adrenergic-mediated action of NEFAs are in agreement with previous findings from Egan et al in humans. This group reported an increase in vascular tone and vascular responsiveness in a 1 -adrenergic stimulation in obese hypertensive patients, [28][29][30] which could not be explained from resistance in the vasodilating action of insulin. 31 Assuming that this increase is caused by NEFA elevation, the investigators studied the infusion of Intralipid and heparin in hand veins of two groups of normotensive subjects.…”
Section: Nefa and A 1 -Adrenergic Activationmentioning
confidence: 90%
“…These observations in favour of an a 1 -adrenergic-mediated action of NEFAs are in agreement with previous findings from Egan et al in humans. This group reported an increase in vascular tone and vascular responsiveness in a 1 -adrenergic stimulation in obese hypertensive patients, [28][29][30] which could not be explained from resistance in the vasodilating action of insulin. 31 Assuming that this increase is caused by NEFA elevation, the investigators studied the infusion of Intralipid and heparin in hand veins of two groups of normotensive subjects.…”
Section: Nefa and A 1 -Adrenergic Activationmentioning
confidence: 90%
“…These studies indicate that lean hypertensive and mostly hypertensive overweight subjects have increased forearm vasodilator response to α-adrenergic blockade by phentolamine as compared with lean normotensive controls, likely reflecting increased sympathetic vascular tone in hypertension [Egan et al, 1987[Egan et al, , 1989. The results in overweight subjects may also reflect increased sympathetic vascular tone associated with increased adiposity.…”
Section: Sympathetic Regulation Of Vascular Function In Obesitymentioning
confidence: 71%
“…Two previous studies by Egan et al [1987; demonstrated increased forearm vasodilatation to phentolamine, a non-selective α-adrenergic receptor antagonist, in lean hypertensive subjects compared to normotensive controls [Egan et al, 1987], and in overweight, mostly hypertensive subjects compared with lean individuals [Egan et al, Figure II.7. Sympathetic neurovascular junction.…”
Section: Sympathetic Regulation Of Vascular Function In Obesitymentioning
confidence: 99%
See 2 more Smart Citations